Dynamic Performance Analysis of Aluminum Matrix Composite Brake Disc for Linear Metro Vehicle - Kailei ZHOU; Wubin CAI; Maoru CHI; Yun LUO (机车电传动)
The dynamic model of a linear motor metro vehicle was established by using multi-body dynamics software. Using Simpack and Simulink co-simulation method and considering the actual traction force, braking force and electromagnetic force on the vehicle, based on the actual needs of the project, the air gap of motor, vibration of motor and axle box as well as various dynamic indexes during coasting, traction and braking of the metro vehicle before and after replacing the cast iron brake disc with the aluminum matrix composite brake disc were analyzed. The results showed that the vibration of the motor and axle box was little influenced by the change of the brake disc, the nonlinear critical speed of the vehicle was slightly increased, the stability and comfort index of the vehicle was little difference, and the lateral force and derailment coefficient of the vehicle were little different before and after the change of the brake disc; Due to the light weight of the replaced aluminum composite brake disc and the reduction of non-sprung mass, the wheel rail vertical force and wheel load reduction rate were improved.